"COMPARISON OF THERAPEUTIC EFFICACY OF MICRONEEDLING WITH PLATELET-RICH PLASMA PLUS 5% MINOXIDIL AND 5% MINOXIDIL ALONE IN ANDROGENETIC ALOPECIA" - Singh, Dr. Harmeet; Talukdar, Dr. Krishna; Narah, Dr. Minakshi; Haridas, Dr. Balu; Boruah, Dr. Porimollika; Roy, Dr. Aparajita; Dr. Pallabi Hatikakoty (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background:Alopecia, a complex dermatological condition, manifests through progressive follicular miniaturization and hair loss, adversely impacting psychological well-being and quality of life. Among its subtypes, androgenetic alopecia (AGA) is the most common form of nonscarring alopecia, largely influenced by genetic predisposition and androgen sensitivity. Despite therapeutic advancements, minoxidil and finasteride remain the only FDA-approved treatments, often limited by variable efficacy, prolonged use, and adverse effects. Platelet-rich plasma (PRP), an autologous biologic enriched with growth factors, has shown promise in hair restoration, although its protocols and long-term efficacy remain under investigation.Aim and Objective:To compare the therapeutic efficacy of 5% topical minoxidil monotherapy versus a multimodal regimen combining minoxidil, microneedling, and autologous PRP in the management of AGA.Methods:Fifty patients (aged 18–50 years) with AGA attending the Dermatology OPD at JMCH were enrolled and divided into Group A (minoxidil alone) and Group B (minoxidil + microneedling + PRP). PRP was administered monthly for six months. Microneedling was performed using a 1.5 mm dermaroller, followed by PRP injections and topical application. Efficacy was assessed via patient self-evaluation, standardized photographs, and Hamilton–Norwood grading at baseline, 3, and 6 months. Informed consent was obtained from all participants.Results:Mean ages were 30.04 years (Group A) and 31.12 years (Group B). Grade III alopecia (52%) was most prevalent. AGA had familial association in 54% of patients. Group B demonstrated significantly superior outcomes at 6 months (P < 0.05). Mild adverse effects included pruritus (16%), seborrheic dermatitis (14%), and headache (12%).Conclusion:The combination of minoxidil, microneedling, and PRP provides superior efficacy over monotherapy. PRP is a safe and effective adjunct, but standardized protocols and larger multicentric studies are warranted.